Making globalization work for the least developed countries / coordinator, Kamal Malhotra ; principal editor, Anita Palathingal. - Malhotra, Kamal; Palathingal, Anita (United Nations Development Programme, 2008)
Globalization and the least developed countries -- Globalization and the least developed countries : issues in trade and investment -- Globalization and the least developed countries : issues in technology -- Globalization, agriculture and the least developed countries -- Energizing the least developed countries to achieve the Millennium Development Goals : the challenges and opportunities of globalization.